Late Occurrence of PML in a Patient Treated for Lymphoma with Immunomodulatory Chemotherapies, Bendamustine, Rituximab, and Ibritumomab Tiuxetan - Michael A. Lane; Vijay Renga; Andrew R. Pachner; Jeffrey A. Cohen (Case Reports in Neurological Medicine)
PML caused by John Cunningham (JC) virus is a rare but an increasingly recognized entity. With the advent of newer immunomodulatory therapies with monoclonal antibodies, there is an increasing incidence of PML. Initially concern was restricted to patients treated for multiple sclerosis with natalizumab but more case reports are being reported during treatment for other conditions like Crohn’s disease and lymphoma with agents such as rituximab. We report the case of a 66-year-old woman who developed PML a year after completion of therapy with rituximab, ibritumomab, and bendamustine.